Specific gravity of Ketapang (Terminallia catappa) according to height level and distant from pith / Hamzah Abidin - Abidin, Hamzah (2004)
Specific gravity (SG) of Sea almond (Terminallia cattapa) was determined using the water displacement method. The specimens used are from three different part of the tree that is base (DBH), middle (50% of the clear bole) and top (before the first branch). The study showed the differentiation of specific gravity of Ketapang at different height. Beside that the effect of specific gravity at different distance from pith also found. The average specific gravity is 0.686. It has the highest specific gravity value at the bottom part of the tree and near specimen to the pith. It is related to density; therefore it has opposite relation with the moisture content. Thus may more research on Ketapang should be perform as it can increase the usage of this non-commercial species in wood industries.